In Optimizing Vocabulary Teaching and Learning for the Third Grade Students of SMP Al Irsyad Pekalongan - Ivan Chabibilah (BRILIANT: Jurnal Riset dan Konseptual, 2020)
This paper focuses on the use of mnemonics technique in teaching and learning English vocabulary. This study aims to know the effectiveness of using mnemonics in helping the students memorizing English vocabulary. Mnemonics is considered to be the most suitable teaching technique as it will give a deeper impression which will lead to the long term memory. Teachers should apply an interesting teaching technique so that the students will have more attention to the material given to them. Based on some language experts, the right teaching technique will give a good atmosphere and great outcome in language acquisition. This paper uses a mix method triangulation. The data were obtained from the quetionnaire, observation before, during and after the implementation of the actions, interview, and the students test scores. The data were in the forms of questionnaire, field notes, observation checklist and students test scores. Then the researcher also tested the normality data analyzed using Sapphiro-Wilk. Independent T-Test used to know wheter the distribution of the data is normal or not. Based on the research result, the application of mnemonics is believed can help students to learn vocabulary and the teacher can teach the students easily as the normality data is normal and the distribution of the data is normal too.